(untitled) (Third Sector Social Economic Review, 2017)
There are currently 80 Sheep and Goat Breeders’ Associations subject to Law No. 5996 in Turkey. A total of 191675 farmers are members of these associations. The aim of this research is to understand the opinions and expectations of goat farms in İzmir, Çanakkale and Balıkesir provinces about the functions of Sheep and Goat Breeders’ Associations. Five districts from each province were included in the research where goat breeding takes place intensively. According to Republic of Turkey Ministry of Food, Agriculture and Lıvestock data, 55% of goat number in Balıkesir is in Merkez, Bigadic, Dursunbey, Sindirgi and Susurluk districts, 60% of goat number in Canakkale is in Merkez, Ayvacik, Bayramic, Ezine and Gelibolu districts, 50% of goat number in Izmir is in Dikili, Karaburun, Kinik, Menemen and Seferihisar districts. Therefore, this districts were included in each province. The main population of the research consists of totally 2,926 farmers found in the districts included in the concept. First of all, in the research, the farmers were divided into three groups. First group consists of farms with 75 goats and less, second group consists of farms with 76- 150 goats while third group consists of farms with 151 goats and more. After the determination of the groups, the proportional sampling formula has been used in order to determine the number of the farmer from each group that will be included in the content of the research and %99 of probability and %5 of error margin have been taken into consideration. As a result of the calculations, 144 farmers from the first group, 33 farmers from the second group, 57 farmers from the third group and 234 farmers in total have been included in the research content. For the determination of the number of farmers to whom the survey will be conducted in each district, the shares of the provinces in terms of the number of the total farmers according to the groups were considered. By this approach, 100 farmers from the province of Canakkale, 73 farmers from the province of Balıkesir, 61 farmers from the province of İzmir were included in the context of the research. The research is based on the production period of 2013. The farms were analyzed according to the groups of the number of animals and groups of the provinces. In the analysis of data, firstly socio-economic characteristics of the farms were examined. After that technical and economic analysis of goat breeding( Number of milked goats, Lactation period, milk yield per animal, milk marketing and goat milk price received by the farmers, variable costs, gross production value and gross margin) were performed. Finally, the types of organization of goat farms, participation durations to associations of goat farms, levels of satisfaction of goat farms about associations activities and expectations of goat farms from associations